Rejuvenation of Aged Pig Facial Skin by Transplanting Allogeneic Granulocyte Colony-Stimulating Factor-Induced Peripheral Blood Stem Cells from a Young Pig. Issue 4 (April 2013) - Harn, Horng-Jyh; Huang, Mao-Hsuan; Huang, Chi-Ting; Lin, Po-Cheng; Yen, Ssu-Yin; Chou, Yi-Wen; Ho, Tsung-Jung; Chu, Hen-Yi; Chiou, Tzyy-Wen; Lin, Shinn-Zong
Following a stroke, the administration of stem cells that have been treated with granulocyte colony-stimulating factor (GCSF) can ameliorate functional deficits in both rats and humans. It is not known, however, whether the application of GCSF-mobilized peripheral blood stem cells (PBSCs) to human skin can function as an antiaging treatment. We used a Lanyu pig ( Sus scrofa ) model, since compared with rodents, the structure of a pig's skin is very similar to human skin, to provide preliminary data on whether these cells can exert antiaging effects over a short time frame. GCSF-mobilized PBSCs from a young male Lanyu pig (5 months) were injected intradermally into the cheek skin of aged female Lanyu pigs, and tissues before and after the cell injections were compared to determine whether this treatment caused skin rejuvenation. Increased levels of collagen, elastin, hyaluronic acid, and the hyaluronic acid receptor CD44 were observed in both dermal and subcutaneous layers following the injection of PBSCs. In addition, the treated skin tissue was tighter and more elastic than adjacent control regions of aged skin tissue. In the epidermal layer, PBSC injection altered the levels of both involucrin and integrin, indicating an increased rate of epidermal cell renewal as evidenced by reductions in both cornified cells and cells of the spinous layers and increases in the number of dividing cells within the basal layer. We found that the exogenous PBSCs, visualized using fluorescence in situ hybridization, were located primarily in hair follicles and adjacent tissues. In summary, PBSC injection restored young skin properties in the skin of aged (90 months) pigs. On the basis of our preliminary data, we conclude that intra dermal injection of GCSF-mobilized PBSCs from a young pig can rejuvenate the skin in aged pigs.